(untitled) (Tabanque. Revista Pedagógica, 2018)
Using video-based motion tracking technology, it is possible to make music without touching a musical instrument, but instead by gesturing in space. With a focus on therapeutic, healthcare and pedagogic contexts, the MotionComposer (MC) is one of a small but growing number of tools being developed today which let all kinds of users participate, including those with different abilities. The aim of the MotionComposer is not just to make a fun trick, but rather to delve into the deeper muscle-music relationships that lie at the heart of healthy music and dance expression. After briefly describing the device, this paper describes some of the therapeutic and pedagogical aspects of its use.